The Dynamics of Growth Opportunity and Investment Opportunity Set on Firm Value Post-COVID-19: : The Role of Capital Structure as an Intervening Variable - Karmelita Indrawati, Novy; Susilo, Hardi (Program Studi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
The food and beverage industry presents unique dynamics, including challenges in distribution, regulations, and consumer trends. This study aims to analyze the effect of Growth Opportunity and Investment Opportunity Set (IOS) on firm value in the food and beverage sector, with Debt-to-Equity Ratio (DER) as an intervening variable. The research employs secondary data analysis and statistical regression using a path analysis approach with SPSS version 26. The results reveal a positive relationship between growth and investment opportunities and firm value, as well as the mediating role of DER in this relationship. DER influences how growth and investment opportunities contribute to enhancing firm value. The sample consists of 14 food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2017–2021 period. The findings provide insight into the importance of financial decision-making in optimizing corporate growth and profitability, and highlight the role of capital structure in mediating the impact of growth and investment opportunities on firm value. This study offers a new perspective on the mediating role of DER, which has not been widely explored in previous research, particularly within the food and beverage sector.